Professor T. Season 2 [videorecording (DVD)] - Piedfort, Paul, 1957-; Baker, Matt (Screenwriter); Miller, Ben, 1966-; Naomi, Emma; White, Barney; Woodward, Sarah; Aubrey, Juliet, 1969-; Gathergood, Andy, 1974-; Reith, Douglas; Stevenson, Juliet; De la Tour, Frances, 1944- (PBS, 2023)
Professor Jasper Tempest and the team untangle a series of knotty crimes ranging from an unexplained fire in a student block to the mystery of an entire family found dead in their home.